FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KELOMPOK TANI HUTAN MITRA UPT KPHP MINAS TAHURA - Gustika, Dian; Suwarno, Eno; Insusanty, Enny (Fakultas Kehutanan Universitas Lancang Kuning, 2020)
The UPT KPHP Minas Tahura is obliged to participate in developing communities around the forest area of ​​its working area which is incorporated in the Forest Farmer Group (KTH). Until now, the performance of KTH is still considered low in managing its members and farming. This study aims to find important factors that influence KTH performance and identify the types of programs that can improve KTH performance. The study was conducted in 4 KTH in Bekalar Village and Belutu Village in Riau Province. The study was conducted using a questionnaire method involving 62 respondents who were analyzed using the Partial Least Square approach. The results showed that KTH performance was classified as moderate. There are 3 factors that have a significant effect on KTH performance, namely group dynamics, member participation and characteristics of group leaders, while the other 3 factors are member characteristics, the role of the instructor and the UPT KPHP Minas Tahura have no significant effect. Furthermore aspects that can support the performance of forest farmer groups are (a) institutional strengthening, (b) enhancing guidance, (c) increasing the ability of farmer group members, and (d) increasing the number of visits, monitoring and evaluation by the UPT KPHP Minas Tahura.